Hepatitis A in children: evaluation of atypical manifestations - Derya Kalyoncu; Nafiye Urganci; Seda Geylani Gulec (Paediatrica Indonesiana, 2020)
Background Although hepatitis A infection is known as a benign, self-limited disease without chronicity, the rate of complications increases over time. Objective To evaluate atypical manifestations of hepatitis A infection in children. Methods A total of 130 children with hepatitis A infection were reviewed. Subjects’ demographic and clinical characteristics, laboratory examinations, and clinical courses were evaluated retrospectively. Results Twenty-one subjects had atypical manifestations of disease as follows: immune thrombocytopenic purpura (1 patient), pleural effusion (1), autoimmune hepatitis and hemolytic anemia (1), nephrotic syndrome (2), meningoencephalitis (2), autoimmune hepatitis (2), acalculous cholecystitis (3), relapsing hepatitis (4), and fulminant hepatitis (5). Only gender was significantly different, with males having more atypical manifestations than females (P=0.03). Mortality rate was 3% (3 patients with fulminant hepatitis and 1 with meningoencephalitis died in the intensive care unit). Conclusion Although hepatitis A virus infection has a benign, self-limited course without chronicity, recognition of atypical cases which carry mortality risk is important.